Cameroon : Staff Report for the 2002 Article IV Consultation, Third Review Under the Poverty Reduction and Growth Facility, and Request for a Waiver of Performance Criterion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This paper evaluates Cameroon's 2002 Article IV Consultation, Third Review Under the Poverty Reduction and Growth Facility (PRGF), and a Request for a Waiver of Performance Criterion. During the first half of the second annual program (October 2001-March 2002), economic activity expanded at a somewhat slower pace than projected, but continued to be strong. Although all the structural benchmarks were observed, the end-March 2002 performance criterion was missed. Good progress continued in implementing policies to strengthen non-oil revenue mobilization, and steps were taken to improve governance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet